Fabrication and mechanotransduction study of pADSCs in 3D scaffold for cultured muscles - Ang, Welthan Wei Hao (Nanyang Technological University, 2024)
With problems of food shortages, resource scarcity, and population increase as global concerns, the need for alternative sources of meat production becomes more pressing. The up-and-coming cultured meat industry has emerged as one plausible solution. The research and development of a suitable scaffold is one of the key steps of growing cultured meat, and for the maturity of current cultured meat processes. In this Final Year Project, nature-derived macromolecules such as alginate, gelatin, and cellulose are chosen as key ingredients for the synthesis of the scaffold, due to their ubiquity. The three materials are mixed together, and varying proportions of each ingredient in the mixture are trialed and produced. Various characterisation techniques are used for analysing the scaffold’s material and structural properties. Mechanical characterisation through compression-mode dynamical mechanical analysis (DMA) and tensile-mode Universal Testing Machine (UTM) was also performed to identify the matrix stiffness, which influences the type of stem cell differentiation which occurs. Other characterisation tools include a cell viability test, as well as fibre diameter analysis under different processing conditions. Overall, based on current findings, the characterisation have shown the alginate-gelatin-cellulose hydrogel mixture to be a viable material for scaffolding applications. However, more work is needed to provide evidence of the long-term viability of the scaffold material.